2000
DOI: 10.1021/ci000061g
|View full text |Cite
|
Sign up to set email alerts
|

DFT/ECP Study of C−H Activation by (PCP)Ir and (PCP)Ir(H)2(PCP = η3-1,3-C6H3(CH2PR2)2). Enthalpies and Free Energies of Associative and Dissociative Pathways

Abstract: (PCP)Ir(H)2 (PCP = eta3-1,3-C6H3(CH2PR2)2) complexes are highly effective catalysts for the dehydrogenation of alkanes; in particular, they are the first efficient molecular catalysts for alkane dehydrogenation that do not require a sacrificial hydrogen acceptor. Using density functional theory/effective core potential methods, we have examined C-H bond cleavage in alkanes and arenes by both (PCP)Ir and (PCP)Ir(H)2. C-H addition to the dihydride is accompanied by loss of H2; both associative and dissociative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 50 publications
7
30
0
Order By: Relevance
“…[130] On the other hand, Goldman concluded that the dehydrogenation reaction takes place via the dissociation of dihydrogen from ( R PCP)IrH 2 , leading to the ( R PCP)Ir (Figure 4, left panel). [131] Goldman×s results satisfactorily explain the experimental results such as no H/D exchange between the hydrogen in ( R PCP)IrH 2 and cyclohexane-d 12 . Although the actual reaction mechanism is still controversial, both studies provide an important consideration in future efforts with respect to the development of related acceptor-less thermal dehydrogenation reactions of alkanes.…”
Section: Reviewssupporting
confidence: 73%
See 1 more Smart Citation
“…[130] On the other hand, Goldman concluded that the dehydrogenation reaction takes place via the dissociation of dihydrogen from ( R PCP)IrH 2 , leading to the ( R PCP)Ir (Figure 4, left panel). [131] Goldman×s results satisfactorily explain the experimental results such as no H/D exchange between the hydrogen in ( R PCP)IrH 2 and cyclohexane-d 12 . Although the actual reaction mechanism is still controversial, both studies provide an important consideration in future efforts with respect to the development of related acceptor-less thermal dehydrogenation reactions of alkanes.…”
Section: Reviewssupporting
confidence: 73%
“…[130,131] Hall predicted that the acceptor-less dehydrogenation of alkanes using [h Figure 4, right panel). [130] On the other hand, Goldman concluded that the dehydrogenation reaction takes place via the dissociation of dihydrogen from ( R PCP)IrH 2 , leading to the ( R PCP)Ir (Figure 4, left panel).…”
Section: Reviewsmentioning
confidence: 99%
“…However, the details of the formation of Ir III (R)(H) from Ir III (H) 2 For both model catalysts, the anthraphos Ir(H) 2 8 studied here and the previously investigated pincer Ir(H) 2 5, the route with the lowest internal energy (lowest barriers and most stable intermediates) passes through the associative path (A). [27] As we began our investigation of the anthraphos model catalyst 8 and examined the relative energies of the A and D paths, we discovered an unexpected TS for an interchange mechanism (I). [27] As we began our investigation of the anthraphos model catalyst 8 and examined the relative energies of the A and D paths, we discovered an unexpected TS for an interchange mechanism (I).…”
Section: Dedicated To Professor Heinz a Staab On The Occasion Of Hismentioning
confidence: 99%
“…The first pincer-iridium-based alkane dehydrogenation catalyst, (PCP)IrH 2 (PCP = κ 3 -C 6 H 3 -2, 6-[CH 2 P(t-Bu) 2 ] 2 ) (1 -H 2 ), was reported by Kaska and Jensen [11] in the mid-1990s, and is active for the transfer dehydrogenation of nalkanes and cycloalkanes, a reaction that we have developed and studied mechanistically [12][13][14][15][16][17]. The initial success of (PCP)Ir in transfer dehydrogenation was followed by the development of a series of (pincer)Ir catalysts with varied steric and electronic properties [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These complexes have been found to effect the oxidative addition of a variety of C-H bonds including those with sp 2 -and sp-hybridized carbon [8][9][10]. Most notable, however, has been the activation of C(sp 3 )-H bonds, leading to alkane dehydrogenation [6,7].The first pincer-iridium-based alkane dehydrogenation catalyst, (PCP)IrH 2 (PCP = κ 3 -C 6 H 3 -2, 6-[CH 2 P(t-Bu) 2 ] 2 ) (1 -H 2 ), was reported by Kaska and Jensen [11] in the mid-1990s, and is active for the transfer dehydrogenation of nalkanes and cycloalkanes, a reaction that we have developed and studied mechanistically [12][13][14][15][16][17]. The initial success of (PCP)Ir in transfer dehydrogenation was followed by the development of a series of (pincer)Ir catalysts with varied steric and electronic properties [18][19][20].…”
mentioning
confidence: 99%